Transcriptional Regulation of Tetrapyrrole Biosynthetic Genes Explains Abscisic Acid-Induced Heme Accumulation in the Unicellular Red Alga Cyanidioschyzon merolae - Kobayashi, Yuki; Tanaka, Kan (Frontiers in Plant Science, 2016)
Abscisic acid (ABA), a pivotal phytohormone that is synthesized in response to abiotic stresses and other environmental changes, induces various physiological responses. Heme, in its unbound form, has a positive signaling role in cell-cycle initiation in Cyanidioschyzon merolae. ABA induces heme accumulation, but also prevents cell-cycle initiation through the titration of the unbound heme by inducing the heme scavenging protein tryptophan-rich sensory protein-related protein O. In this study, we analyzed the accumulation of tetrapyrrole biosynthetic gene transcripts after the addition of ABA to the medium and found that transcripts of a ferrochelatase and a magnesium-chelatase subunit increased, while other examined transcripts decreased. Under the same conditions, the heme and magnesium-protoporphyrin IX contents increased, while the protoporphyrin IX content decreased. Thus, ABA may regulate the intracellular heme and other tetrapyrrole contents through the transcriptional regulation of biosynthetic genes.